Adapting legal cultures - Nelken, David; Feest, Johannes (Oñati international series in law and society., 2001)
This exciting collection looks at the theory and practice of legal borrowing and adaptation in different areas of the world: Europe, the USA and Latin America, S.E. Asia and Japan. Many of the contributors focus on fundamental theoretical issues. What are legal transplants? What is the role of the state in producing socio-legal change? What are the conditions of successful legal transfers? How is globalisation changing these conditions? Such problems are also discussed with reference to substantive and specific case studies. When and why did Japanese rules of product liability come into line wi.